2007
DOI: 10.1063/1.2712180
|View full text |Cite
|
Sign up to set email alerts
|

Numerical calculations of the total ac loss of Cu-stabilized YBa2Cu3O7−δ coated conductor with a ferromagnetic substrate

Abstract: A numerical model is developed to calculate the total alternating-current (ac) loss of Cu-stabilized YBa2Cu3O7−δ (YBCO) coated conductors with a ferromagnetic substrate when carrying an alternating transport current in an ac background magnetic field. The time evolutions of current and magnetic field distributions along the width of the conductor are calculated by solving the one-dimensional Poisson equation for the magnetic vector potential. In addition to the ac loss dissipated in the superconducting layer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…In Fig. 6(a) and (b), the agreement between the computed values of ac loss and the measured ones is an improvement on earlier work [21]. Further improvement is possible in the model by including: 1) the magnetic field dependence of critical current J c and 2) a realistic B-H behavior of the weakly ferromagnetic substrate, which is challenging, as it would require modeling both the nonlinearity and the hysteresis.…”
Section: Weakly Ferromagnetic Substratesupporting
confidence: 54%
“…In Fig. 6(a) and (b), the agreement between the computed values of ac loss and the measured ones is an improvement on earlier work [21]. Further improvement is possible in the model by including: 1) the magnetic field dependence of critical current J c and 2) a realistic B-H behavior of the weakly ferromagnetic substrate, which is challenging, as it would require modeling both the nonlinearity and the hysteresis.…”
Section: Weakly Ferromagnetic Substratesupporting
confidence: 54%
“…Similar to the measurements conducted by Duckworth et al [14], [15], the results also show that the contribution of ferromagnetic loss is significant for peak current ratio below 0.4. The detailed studies on temperature and frequency dependence of ac transport losses in YBCO tape and a comparison with the loss behavior of BSCCO tape were published previously [16], [17].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the eddy current loss at low temperatures is considerably smaller. Mathematically, both analytical [25] and numerical [26] models have shown that eddy current loss in metal layers (e.g., stabilizers) assembled in a thin strip superconductor strongly depends on the normalized field , where is a characteristic field determined from and the width, 2 , of the thin strip tape, . At low temperature, high causes high or small .…”
Section: Magnetization Ac Loss At Variable Temperaturesmentioning
confidence: 99%
“…In the simulation, the sample superconducting properties are assumed to follow the power-law characteristics determined by fitting the experimental current-voltage ( -) curve. The detailed mathematical formulation and calculation procedure of the numerical model were reported explicitly in [26]. As seen in Figs.…”
Section: Total Ac Loss At Variable Temperaturementioning
confidence: 99%